2019
DOI: 10.4149/bll_2019_056
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma microRNAs and serum trace elements levels in primary hyperlipidemia

Abstract: The aim of the study was to investigate the relationship between plasma microRNA expression levels, which are associated with lipid metabolism and serum trace element levels in patients with primary hyperlipidemia. METHODS: This study was performed on 46 (21M / 25F) primary hyperlipidemia patients aged 25-65 years and 37 (18 M/19 F) healthy people aged 25-65 years. RESULTS: The following miRNAs were upregulated: miR-33a-5p, miR-370-5p, miR-378a-3p, miR-27a-3p, miR-27a-5p and miR-335-5p. Additionally, the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It is quite certain that many new glycosylation disorders are awaiting their identifi cation since it is estimated that more than 500 genes, approximately 0.5 to 1% of the translated human genome, participate in oligosaccharide synthesis and function. For that reason, defects in glycosylation pathway need to be considered more often as the cause of these disorders and physicians need to be aware of them, know their limitations and appropriate way of management (19). Furthermore, the development of animal models offers the potential to test therapeutic approaches and will be helpful in understanding the pathogenesis of these disorders (6).…”
Section: Resultsmentioning
confidence: 99%
“…It is quite certain that many new glycosylation disorders are awaiting their identifi cation since it is estimated that more than 500 genes, approximately 0.5 to 1% of the translated human genome, participate in oligosaccharide synthesis and function. For that reason, defects in glycosylation pathway need to be considered more often as the cause of these disorders and physicians need to be aware of them, know their limitations and appropriate way of management (19). Furthermore, the development of animal models offers the potential to test therapeutic approaches and will be helpful in understanding the pathogenesis of these disorders (6).…”
Section: Resultsmentioning
confidence: 99%
“…Obesity-associated exosomal miRNAs are important in the pathogenic mechanism of glucose intolerance and dyslipidemia [16]. Overexpression of miR-27a-3p may cause obesity and dyslipidemia [17]. Overexpression of miR-107 may regulate the insulin signaling pathway and cause the imbalance of glucose homeostasis [18].…”
Section: Expression and Role Of Pdk4 On Childhood Dyslipidemia And Li...mentioning
confidence: 99%
“…In the last decade, very few ionomics studies have been conducted for hyperlipidemia patients. Yerlikaya et al found that lower levels of essential elements (Cr, Fe, Mn, Mo, and Se) as well as higher levels of Co, Ni, and Cd in serum are associated with an increased risk of primary hyperlipidemia, suggesting an important role of these elements in the regulation of lipid homeostasis ( 224 ). On the other hand, several studies have either confirmed previous observations or revealed additional elements that are associated with hyperlipidemia.…”
Section: Recent Progress In Ionomics Of Metabolic Diseasesmentioning
confidence: 99%